Pengaruh Perceived Organizational Support dan Work-Life Balance terhadap Employee Engagement dengan Mediasi Kepuasan Kerja : (Studi pada Karyawan Support Unit PT Kurnia Ciptamoda Gemilang Kebayoran Lama Jakarta Selatan) - Nahdiah Nahdiah; Zulvia Khalid (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the effect of perceived organizational support and work-life balance on employee engagement with mediation of job satisfaction at PT Kurnia Ciptamoda Gemilang Kebayoran Lama South Jakarta. The sample in this study were 65 employees support unit of PT Kurnia Ciptamoda Gemilang. Data was collected through a questionnaire using google form. The sampling technique used in this study is the saturated sampling method (total sampling). Data analysis in this study used structural equation modeling (SEM) with SmartPLS version 4.1. Hypothesis testing with the PLS approach, carried out in two stages, namely testing the outer model and inner model. The results of this study indicate that Perceived Organizational Support has a significant effect on Employee Engagement while the Work-Life Balance and Job Satisfaction variables have an insignificant effect on Employee Engagement.